2012
DOI: 10.2478/v10034-012-0005-z
|View full text |Cite
|
Sign up to set email alerts
|

Cag Repeat Number in the Androgen Receptor Gene and Prostate Cancer

Abstract: Prostate cancer (PC) is the second leading cause of cancer deaths in men. The effects of androgens on prostatic tissue are mediated by the androgen receptor (AR) gene. The 5′ end of exon 1 of the AR gene includes a polymorphic CAG triplet repeat that numbers between 10 to 36 in the normal population. The length of the CAG repeats is inversely related to the transactivation function of the AR gene. There is controversy over association between short CAG repeat numbers in the AR gene and PC. This retrospective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
(30 reference statements)
0
7
0
1
Order By: Relevance
“…Regarding South American countries, Brazil reported an average of 20.65 CAGs for a population of Caucasian and African descents (37). In another study, Madjunkova et al (38) reported a mean repeat length of 21.5 CAGs in patients with PC from Macedonia. In a study that examined adenocarcinomas, the number of CAG repeats ranged from 12 to 30 and averaged 20, which was similar to that in a healthy Brazilian population.…”
Section: Discussionmentioning
confidence: 96%
“…Regarding South American countries, Brazil reported an average of 20.65 CAGs for a population of Caucasian and African descents (37). In another study, Madjunkova et al (38) reported a mean repeat length of 21.5 CAGs in patients with PC from Macedonia. In a study that examined adenocarcinomas, the number of CAG repeats ranged from 12 to 30 and averaged 20, which was similar to that in a healthy Brazilian population.…”
Section: Discussionmentioning
confidence: 96%
“…10 Another confounding factor is a broad diversity of cut-off values of repeat number considered "optimal" for the prediction of PC in series published to date. 7,8,11 We chose the cut-off values identical with those in the study of Mononen et al 9 Furthermore, our study recognized a GGN repeat count of 19 or lower as predisposing to PC. This relationship was also confirmed by Zeegers et al 10 ; however, as with the (CAG) n region, there is no consensus on the number of GGN repeats most predictive for PC.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 This phenomenon is believed to predefine the sensitivity of peripheral tissue to circulating androgen, possibly influencing the susceptibility to PC along with clinical and pathological characteristics of the tumor. [7][8][9] Introduction Prostate cancer (PC) is a major health problem among men in Western countries. The incidence of this tumor has been rising in most industrialized countries, including Poland, although in the United States, the number of new PC cases has declined slightly in recent years, 1,2 along with a similar trend in mortality.…”
mentioning
confidence: 99%
“…The effects of androgens are mediated through the androgen receptor (AR), a nuclear transcription factor encoded by the AR gene. Mutation and polymorphism in androgen has been reported to precipitate either male infertility or prostate cancer [29,[38][39][40][41][42]. The differences in CAG and GGN tender repeats in androgen receptor polymorphism have been implicated in ethnical diversity observed in the risk factors of prostate cancer [29].…”
Section: Male Infertility and Prostate Cancermentioning
confidence: 99%